STRATEGI PEMERINTAH KOTA METRO DALAM UPAYA PENINGKATAN BUDAYA CINTA LINGKUNGAN MENUJU PEMBANGUNAN KOTA YANG BERKELANJUTAN - Yerri Noer Kartiko (Nizham Jurnal Studi Keislaman, 2016)
Strategic Efforts of Metro City Government for Public Cultural Improvement in Environmental Awareness towards Development based Green Economy Concept. Both government and public have very important role and responsibility in management and preservation of environment. Therefore, in preservation of environment matters, Governmet and public shall have sinergetic and mutualism relationship. Government shall empower public to take an active role play in effort for preservation of environment. In the other hands, Government shall consider public’s needs in formulation and promulgation public policy, strategic planning in preservation of environment. Up to this time, Metro City Government performs any kind of public policy for mindset and cultural set shifting in order to enhance public awareness in environment preservation. These strategics efforts iniated by budgeting arrangement, public empowerment, public policy and law enforcement of environment preservation